Fullerene-Based n-Type Materials That Can Be Processed by a Photoprecursor Approach for Photovoltaic Applications. (25th January 2017) - Kawajiri, Kazuki; Kawanoue, Takahiro; Yamato, Masaki; Terai, Kengo; Yamashita, Masataka; Furukawa, Mari; Aratani, Naoki; Suzuki, Mitsuharu; Nakayama, Ken-ichi; Yamada, Hiroko
Abstract : The active layer of organic photovoltaic cells (OPVs) is typically a blend of p- and n-type semiconductors, and the arrangement of these materials largely affects the device performance. We have recently proposed a unique deposition technique in which α-diketone-type photoprecursors are solution-deposited and then subjected to in-situ photoreaction to form acene-based semiconductors, as an effective means for controlling the morphology and vertical composition profile in organic molecular blends. However, the applicability of this "photoprecursor approach" has been limited to p-type materials so far, restricting the flexibility in designing photovoltaic layers. Herein, we report α-diketone-type photoprecursors of two fullerene–anthracene conjugates which have been designed to serve as n-type material in OPVs. The new α-diketones, named N601DK and N602DK, are successfully applied to the photoprecursor approach, affording smooth thin films of the corresponding photoreaction products N601 and N602. The n-type materials thus produced are evaluated in bulk-heterojunction (BHJ) OPVs and found to show good photovoltaic response. Especially, N601 performs as well as PC61 BM, a fullerene-based benchmark n-type material. These results will serve as a basis for further improvement of OPVs through optimization of the molecular arrangement in solution-processed photovoltaic layers.